2001
DOI: 10.1128/mcb.21.4.1393-1403.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α (Nuclear Receptor 2A1) Is Essential for Maintenance of Hepatic Gene Expression and Lipid Homeostasis

Abstract: The numerous functions of the liver are controlled primarily at the transcriptional level by the concerted actions of a limited number of hepatocyte-enriched transcription factors (hepatocyte nuclear factor 1␣ [HNF1␣], -1␤, -3␣, -3␤, -3␥, -4␣, and -6 and members of the c/ebp family). Of these, only HNF4␣ (nuclear receptor 2A1) and HNF1␣ appear to be correlated with the differentiated phenotype of cultured hepatoma cells. HNF1␣-null mice are viable, indicating that this factor is not an absolute requirement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
957
3
31

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,038 publications
(1,053 citation statements)
references
References 72 publications
62
957
3
31
Order By: Relevance
“…Furthermore, IPA upstream regulator analysis suggested that the factors driving the differential gene expression between the INT and MF diet were TGFB1 and a number other cytokines including TNF, IL4, and IFNγ. On the contrary, differential gene expression between INT and CR‐ exposed mice was due to NFE2L2 (or NRF2) activity well‐known for its antioxidant response 52, XBP1, acknowledged to mediate ER stress/apoptosis 53, 54, and the well‐established liver the liver transcription factor HNF4A 55. Remarkably, our data do not point toward the involvement of one or more of the four well‐established pathways involved in mediating the CR effect including (1) the insulin like growth factor (IGF‐1)/insulin signaling pathway, (2) the sirtuin pathway, (3) the adenosine monophosphate activated protein kinase pathway, and (4) the target of rapamycin pathway 6, 56, as upstream regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, IPA upstream regulator analysis suggested that the factors driving the differential gene expression between the INT and MF diet were TGFB1 and a number other cytokines including TNF, IL4, and IFNγ. On the contrary, differential gene expression between INT and CR‐ exposed mice was due to NFE2L2 (or NRF2) activity well‐known for its antioxidant response 52, XBP1, acknowledged to mediate ER stress/apoptosis 53, 54, and the well‐established liver the liver transcription factor HNF4A 55. Remarkably, our data do not point toward the involvement of one or more of the four well‐established pathways involved in mediating the CR effect including (1) the insulin like growth factor (IGF‐1)/insulin signaling pathway, (2) the sirtuin pathway, (3) the adenosine monophosphate activated protein kinase pathway, and (4) the target of rapamycin pathway 6, 56, as upstream regulators.…”
Section: Resultsmentioning
confidence: 99%
“…As conventional gene knock-out is lethal, Hayhurst et al (2001) addressed the role of HNF4a in mature hepatocytes using a conditional gene knockout. Mice lacking hepatic HNF-4a exhibit major perturbations of lipid metabolism with increased accumulation of lipid in the liver and reduced plasma cholesterol and triacylglycerol concentrations.…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…HNF4α (hepatocyte nuclear factor 4α) is a liver-enriched member of the nuclear receptor superfamily that regulates the expression of genes involved in fatty acid, cholesterol and glucose metabolism, apolipoprotein synthesis and liver development [1][2][3]. HNF4α regulates the expression of genes in liver, both directly and indirectly, through interaction with other HNFs, including the variant homeodomain protein HNF1α, C/EBPs (CCAAT/enhancerbinding proteins), HNF3 winged helix factors and the one-cut homeoprotein, HNF6 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the HNFs, HNF4α is proposed to play a central role in the regulation of liver-enriched transcription factors and their liver-specific targets, including liver CYP (cytochrome P450) genes [5]. The key regulatory role of HNF4α was demonstrated in a liver-HNF4α-deficient mouse model [2], in which HNF4α was shown to control the expression of HNFs in vivo in both a positive manner (HNF1α, C/EBPα and C/EBPβ) and a negative manner {HNF3α, HNF3β, HNF6 and the HNF4α coactivator, PGC-1α [PPARγ (peroxisome-proliferator-activated receptor γ ) co-activator-1 α]} [6].…”
Section: Introductionmentioning
confidence: 99%